2012
DOI: 10.1007/s10461-012-0386-8
|View full text |Cite
|
Sign up to set email alerts
|

Documentation of Psychiatric Disorders and Related Factors in a Large Sample Population of HIV-Positive Patients in California

Abstract: This retrospective cohort study examined electronic medical records of HIV-positive patients in California (N=7,834) to find the prevalence of any psychiatric condition and the associations between several factors and the likelihood of these disorders. Approximately 53% of the patients in this study had a documented psychiatric condition, including 23% who had a mood disorder, 19% who had a substance-related disorder, and 16% who had an anxiety disorder. After controlling for potential confounders, significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 45 publications
2
10
2
Order By: Relevance
“…Consistent with prior studies [38,5861], we found an elevated point prevalence of depressive symptoms among HIV-positive participants who had a history of depression and among those who were: female, younger, recreational drug users, or unemployed/disabled. Unlike the U.S. evidence [58,61], we did not note differences among ethnocultural minorities.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Consistent with prior studies [38,5861], we found an elevated point prevalence of depressive symptoms among HIV-positive participants who had a history of depression and among those who were: female, younger, recreational drug users, or unemployed/disabled. Unlike the U.S. evidence [58,61], we did not note differences among ethnocultural minorities.…”
Section: Discussionsupporting
confidence: 91%
“…When compared to prior studies, our results on the point prevalence of current depressive symptoms (28%) are comparable to recent findings (23–26%) from large-scale studies conducted in the U.S. [58,72,73]. However, our results showed a lower recurrence rate of 43% when compared to the 61% rate found by Malee et al(2014) [39] and to the 90% rate found by an older study conducted by Johnson and colleagues (1999) [40].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In fact, elevated anxiety symptoms were less prevalent in WIHS (9%) compared to SWAN (~30%). Although the low rates of anxiety in the WIHS may be surprising, studies of HIV-infected individuals show that African-Americans are at a lower risk for anxiety and other psychiatric disorders compared to other ethnicities 50-52 perhaps due to reporting biases. One possible mechanism linking anxiety to decreased verbal memory in HIV-infected women is a female vulnerability to the negative effects of stress hormones on verbal memory.…”
Section: Discussionmentioning
confidence: 98%
“…Studies have shown that PLWH have more mental health problems than the general population, with a two to five times higher prevalence of depression, anxiety, and suicide, as well as higher harmful substance use (Brandt, 2009;Parhami, Fong, Siani, Carlotti & Khanlou, 2013;.…”
Section: Introductionmentioning
confidence: 99%